Nuclear Dilemma in the middle east - İçöz, Ersin (My University, 2011)
ORTA DOĞU’DA NÜKLEER SORUNSALI Bu tez çalışması nükleer enerji ve nükleer silahlar arasındaki ilişkiyi Orta Doğu perspektifinden incelemektedir. Orta Doğu’daki ülkelerin nükleer enerji planları ve özellikle İran’ın nükleer nde, bu bölgenin gelecekte nükleer sorunsalı ile karşılaşması yüksek bir ihtimaldir; ve bu sorunsalın merkezinde barışçıl yollarla nükleer enerji kullanımı ile nükleer silahların yayılımı arasındaki nükleer eşik olacaktır. Bu tezin amacı, bölge içerisinde nükleer enerjinin barışçıl yollarla kullanımını destekleyerek, nükleer enerji ve nükleer silahlar arasında, Orta Doğu’daki nükleer bilmecenin perspektifinden bir köprü kurmak, geçmiş tecrübeleri ve karar verme mekanizmalarını yorumlamaktır. 1992 ve 1995 yılları arasında aktif olan Silahların Kontrolü ve Bölgesel Güvenlik gibi bir çalışma grubunun yardımı ile Orta Doğu’da kitle imha silahlarından arındırılmış bölgenin kurulması; ve bu bölge içerisindeki tüm fisyon maddelerinin tek sahibi olarak, uranyum zenginleştirilmesi ve plutonyum ayrıştırılması üzerinde koruma sağlamak için, tedarik ajansının kurulması sonuçlarına ulaşılmıştır. kleer Enerji, Nükleer Silahlar, Nükleer Enerji Rönesansı, Nükleer Eşik, İran’ın Nükleer Orta Doğu, Nükleer Silahların Yayılmasının Önlenmesi Antlaşması, Nükleer Silahtan Arındırılmış Bölge

NUCLEAR DILEMMA IN THE MIDDLE EAST This thesis examines the relations between nuclear energy and nuclear weapons from the perspective of the Middle East. It argues that considering the nuclear energy plans of the countries in the Middle East, especially the nuclear program of Iran, it is highly possible that this region would face with the nuclear dilemma in the future; and at the center of this dilemma there would be the nuclear threshold between peaceful use of nuclear energy and nuclear proliferation. The aim of this thesis is to build a bridge between nuclear energy and nuclear weapons from the perspective of nuclear conundrum in the Middle East and to evaluate past experiences and decision making mechanisms by providing a support for the promotion of peaceful use of nuclear energy within the region. It is concluded that the Middle East Weapons of Mass Destruction Free Zone should be established with the help of a working group such as Arms Control and Regional Security which was active between 1992 and 1995; and the supply agency should be established as the only owner of all fissile materials within the zone to provide a protection over uranium enrichment and plutonium separation. Nuclear Energy, Nuclear Weapons, Nuclear Energy Renaissance, Nuclear Threshold, the Nuclear Program of Iran, Middle East, the Nuclear Nonproliferation Treaty, Nuclear Weapon Free Zone
Keywords: Nükleer Enerji; Ortadoğu